Kapasitas Hukum Pasien Non Covid dalam Penegakan HAM di Indonesia - Muhammad Natsir (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
The Covid-19 pandemic has brought many changes in the life system of people in Indonesia. In this case, the health sector and hospitals as facilities and infrastructure for health facilities providers have many challenges so as not to become the main victims in the spread of this pandemic. Furthermore, as a mitigation effort in continuing the Presidential Decree of the Republic of Indonesia Number 11 of 2020 concerning the Determination of the Corona Virus Disease 2019 (COVID-19) Public Health Emergency, several strategies have been carried out. Still, due to this integrated strategy”s focus, several media reports show the reality of other problems that have been neglected in perspective law. One of the unlucky cases is the death of pregnant women due to negligence of the hospital in handling the first delivery after being rejected by seven hospitals and another case in the form of providing non-Covid-19 patients, which then becomes a big problem in upholding human rights. This study aims to examine further the extent to which this matter is regulated in the legal system in Indonesia, the main responsible strategies and institutions, and other aspects that can be found in this confusion of problems. For this reason, researchers use the Goal Free Evaluation Framework as an independent form of the goals to be achieved in the Human Rights Law and to see other sides that will be found during the evaluation of the issue of human rights violations. The results obtained are that human rights have been regulated from the acceptance of health services by the community and labor laws from the medical team and hospital strategies listed in Service Operational Standards but have not been fully implemented. As for this matter, then it becomes the responsibility of the regional government in minimizing the occurrence of human rights violations as the institution that is most closely attached to the community even though there is a national human rights commission that is tasked with further reviewing the problem, especially after finding other factors that arise from these cases. Cases in hospitals during the Covid-19 pandemic. The main objective of this research is to serve as an evaluation material for health institutions. The other objective is to recommend it to institutions and legal observers in Indonesia to strengthen regulation and law enforcement in Indonesia